Restrictions In Conventional Asepsis as a Result of Protective Gear During Covid – Effects on Postoperative Infections - Kaur, Gagandeep; Shetty, Suprajna; Ballal, Priya; Srivastava, Saumya (Journal of Neonatal Surgery, 2025)
Background: The novel coronavirus disease which is caused by SARS CoV 2 became a pandemic and several measures were implemented to contain/prevent its transmission like use of N95 mask, face shield, use of Personal Protective equipment (PPE). The PPE is meant to reduce the transmission of infection from the patient to healthcare workers and to other patients. The surgeons sanitize their hands with alcohol-based solution and wear sterile scrubs over the PPE and perform the surgery. The concept of scrubbing is not applicable when operating in a PPE. The problem arises during surgical management of such cases as PPE causes discomfort and visualization difficulties. This study is therefore aimed at determining if the incidence of surgical site infection has increased despite having stringent hygiene methods and restricted movement of staff and relatives. Aims and Objectives: To study and compare the surgical site infection (SSI) risk in patients undergoing obstetric and gynaecological surgical procedures during the pre-COVID and COVID era. Materials and methods: The study was a retrospective observational study conducted at Lady Goschen Hospital, Mangalore which is a tertiary care centre of Dakshinna Kannada and serves as a referral centre for other hospitals, under the Department of OBG, Kasturba Medical College, Mangalore. The study participants were divided into 2 groups. Group 1 comprising of patients operated at Lady Goschen Hospital in the COVID free period from March 2019 to February 2020 and developed SSIs and the Group 2 comprising of patients operated during COVID era from March 2020 to February 2021 and developed SSIs. Inclusion criteria: All the patients undergoing obstetric and gynaecological surgical procedures who developed SSIs. Method: The study was conducted by going through the medical records of the patients operated during the study period and will be assessed for the associated risk factors, type of SSI, and the management done for the SSI. The proportion in the two groups will then be assessed and compared. Results: In the two study groups, no significant difference was found in the demographic data. The mean BMI between both the groups were also not significant. Some of the risk factors identified were presence of medical disorders like diabetes, hypertension complicating pregnancy. The duration of surgery showed no statistical significance. There was an increase in SSI in the COVID -19 period when compared to pre-pandemic period hence leading to an increased need of secondary suturing.